Select Profiles of Indian Businessmen: A Sprinkling From The Past - Sudhakar, G. P. (Journal of Commerce and Trade, 2022)
India has a long history of business and international trade that spans 4000 years, however, profiles of ancient businessmen are rarely available to students to help them visualize a person and environment of an earlier era. This article has short profiles of businessmen across many centuries based on ancient texts, recent findings of ancient inscriptions and other recorded history. The case stories will hopefully provide human faces to help understand business history and the unique business practices in India. The practice of 'Dana' and the hindu suggestion to businessmen to return some of the profits for the welfare of society can be seen from most profiles. The article is barely representative with numerous recent findings of inscriptions across India, Indonesia, South East Asia that refer to Indian Businessmen, however an attempt was made to capture profiles from across the timeline. The article has short introductions to Saddalputra, Ananthapindaka, Dhannavriddhi, Nagarshrestin Ribhupala, Jagat Sheth, Chatti Setti, Dhananjaya, Kaundinya, Jagdu Shah and Elelasingan. Classification-JEL: G10